Is Training more Frequent when Wage Compression is Higher? Evidence from 11 European Countries - Giorgio Brunello (Center for Economic Studies and ifo Institute (CESifo), 2002)
In this empirical paper, I use the 1996 wave of the ECHP dataset to investigate the relationship between measures of wage compression and training incidence in 11 European countries. After controlling for individual factors and country specific institutional differences, I find evidence of a positive and significant relationship between wage compression and training, both firm-specific and general. While the finding for firm-specific training is consistent with both competitive and non-competitive approaches, the result for general training is only consistent with the non-competitive approach.
Keywords: 330; training; Europe